Correlation Between Physical Activity, Body Composition, And Micronutrition Intake In Patients Of Knee Osteoarthritis At The Medical Rehabilitation Clinic, Fatmawati Hospital Jakarta In 2021 - Wilis Laksari Putri Adjie; David Renardo Tidja (The Avicenna Medical Journal, 2022)
Background : Osteoarthritis (OA) is a degenerative joint disease associated with joint cartilage damage that usually occurs in the aging process. This study is to analyze the correlation between physical activity, body composition, and the micronutrients intake such as vitamin C, D, E, and Calsium the patients with knee OA at the Medical Rehabilitation Clinic (MRC) at Fatmawati Hospital, Jakarta in 2021.Methods: This is a cross sectional quantitative research. The samples were 45 patients who have been diagnosed with knee osteoarthritis in outpatient medical rehabilitation clinic at Fatmawati General Hospital Jakarta who met the inclusion criteria.Results : the results of statistical tests showed that there was a significant difference in the average percentage of body fat with the gradation of OA patients, p value = 0.004. However, there was no significant difference between the average physical activity score, and intake of macronutrients (energy, protein, fat and carbohydrates), BCAAs (arginine and histidine), and intake of micronutrients (vitamin C, vitamin D, vitamin D, vitamin E and Calcium)Conclusion: Percent body fat is the variable with the highest correlation among other factors.